Hombrecitos - Alcott, Louisa May, 1832-1888. (Buenos Aires : Grupo Editorial Luman, 2001)
Both boys and girls find a happy, rollicking home at Plumfield, a remarkable school founded by Jo and Father Bhaer.
Keywords: Spanish language materials -- Juvenile fiction; Family life -- Fiction; New England -- Fiction